2006
DOI: 10.1016/j.jvs.2006.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of limbs with arterial insufficiency and chronic ulceration treated without revascularization

Abstract: Limb salvage can be achieved in most patients with arterial insufficiency and uncomplicated chronic nonhealing limb ulcers using a program of wound management without revascularization. Healing proceeds slowly, however, requiring more than a year in many cases. Patients with an ABI <0.5 are more likely to require amputation. Interventions designed to improve outcomes in critical limb ischemia should stratify outcomes based on hemodynamic data and should include a comparative control group given the natural his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
177
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(193 citation statements)
references
References 20 publications
8
177
1
4
Order By: Relevance
“…Within a year of diagnosis, Ϸ20% of patients will die, 35% will require amputation, and the remainder will enter a more chronic state. 29,30 Prospective definition of these subpopulations is problematic and often imprecise, and these difficulties must be addressed during trial design and data analysis. A similar challenge is encountered with variability within the more chronic group that tends to be represented in clinical trials.…”
Section: Article P 58mentioning
confidence: 99%
“…Within a year of diagnosis, Ϸ20% of patients will die, 35% will require amputation, and the remainder will enter a more chronic state. 29,30 Prospective definition of these subpopulations is problematic and often imprecise, and these difficulties must be addressed during trial design and data analysis. A similar challenge is encountered with variability within the more chronic group that tends to be represented in clinical trials.…”
Section: Article P 58mentioning
confidence: 99%
“…10,11 The correlation of low TP with increased mortality and decreased amputation free survival (AFS) has been demonstrated in patients with incompressible leg arteries. 12,13 In addition to AP and ABI, TP is used in the widely accepted TransAtlantic Inter-Society Consensus II (TASC II) classification of limb ischaemia.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that limb salvage can even be achieved without revascularization in most patients with arterial insufficiency and uncomplicated chronic nonhealing limb ulcers when we treat them only with appropriate conservative management. 21 Against this background, and based on our results, maintaining Position III, sitting with the foot lowered vertically, may be ideal for the peripheral arterial circulation and a valuable, manageable option for patients with end-stage PAD. We do not usually pay attention to the body position of the patients, but it may be useful to consider positioning as adjunctive management.…”
Section: Discussionmentioning
confidence: 81%